Exploring the extent of transformational leadership in the context of Miri entrepreneurs - Krishnan, Anbalagan; Lew, Tek Yew; Muniapan, Balakrishnan; Kong, Eunice Eik Fong (2004)
In this century entrepreneurs (leaders) are faced with significant challenges that require extraordinary leadership. The business environments are changing at a very fast pace with immense competition, changing needs of customers, increasingly global economy and the rapid changes in the technology. This paper investigates the transactional and transformational leadership styles among the Miri entrepreneurs by employing the approach based on the Bass’s Multifactor Leadership Questionnaire (MLQ). Miri was chosen as the area of study as it will be a resort city by the year 2005 and, hence, Miri needs entrepreneurs who demonstrate effective leadership styles to cope with the increasing dynamic and complex business environment. Moreover, the entrepreneurs must meet the increasing preference for transformational leadership styles among employees found in many studies in order to improve satisfaction and commitment of the workforce. The findings were mapped with various literatures with the intention to enhance understanding of the leadership styles of Miri entrepreneurs and to further promote effective leadership styles amongst them. This research identified the leadership style of Miri entrepreneurs as transformational rather than transactional. This finding is consistent with the findings of transformational and transactional leadership styles in the Malaysian context undertaken by Sheh (2002) and Ng et al. (2002).